Fluororesin film, metal-coated laminate, and circuit substrate
By controlling the number of conductive foreign matter and unstable functional groups in the fluororesin film, and using PFA or FEP as the fluororesin resin, the problem of poor adhesion with metal foil is solved, and a circuit substrate with low transmission loss and high performance is achieved.
Patent Information
- Application Number
- CN202380053957.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-07-22
- Filing Date
- 2023-07-24
- Publication Date
- 2025-02-28
AI Technical Summary
In the prior art, it is difficult to obtain a fluororesin film that is well bonded to metal foils such as copper foils, which leads to problems such as easy breakage of signal lines and high transmission losses.
A film composed of fluororesin is used, and the number of conductive foreign matters having a length or width direction of 50 μm or more in the length of the film is less than 60 per square meter, and the number of unstable functional groups is preferably less than 350. Tetrafluoroethylene/perfluoro(alkylvinyl ether) copolymer (PFA) or tetrafluoroethylene/hexafluoropropylene copolymer (FEP) is used as the fluororesin, and the area is preferably 1 square meter or more.
Good bonding between the fluororesin film and the metal foil is achieved, reducing the breakage and transmission loss of the signal line, and improving the performance of the circuit substrate.
Smart Images

Figure BDA0005242961150000241 
Figure BDA0005242961150000251
Abstract
Description
Technical Field
[0001] The present disclosure relates to a fluororesin film, a metal-clad laminate, and a circuit board. Background Art
[0002] In circuit boards, there is a demand for low transmission loss boards that are less likely to cause disconnection of signal lines. Therefore, there is a general demand for films that adhere to copper foil without deformation, and conventionally, some films with no surface irregularities and good appearance have been proposed (Patent Documents 1 to 3).
[0003] Among them, for example, Patent Document 1 proposes a film roll having an arithmetic mean surface roughness of 0.1 μm or less on both surfaces and a winding deviation of 5 mm or less in the axial direction with respect to a winding core.
[0004] Patent Document 4 describes that: by making the terminal groups other than -CF3 groups of the fluorinated copolymer used for electric wire applications 6 The number of carbon atoms is 50 or less, and there is no foaming due to thermal decomposition during extrusion molding, which can reduce molding defects. In addition, the recombination (crosslinking) of the molecules of the fluorinated copolymer during extrusion molding that causes fish eyes will not occur, which can reduce the number of fish eyes.
[0005] Prior art literature
[0006] Patent Literature
[0007] Patent Document 1: Japanese Patent Application Publication No. 2021-160856
[0008] Patent Document 2: International Publication No. 2017 / 022575
[0009] Patent Document 3: Japanese Patent Application Publication No. 2017-119741
[0010] Patent Document 4: International Publication No. 2008 / 047906 Summary of the invention
[0011] Problems to be solved by the invention
[0012] An object of the present disclosure is to obtain a fluororesin film having good adhesion to a metal foil such as copper foil, and a metal-clad laminate using the fluororesin film.
[0013] Means for solving problems
[0014] The present disclosure relates to a fluororesin film, which is a film composed of a fluororesin, wherein the number of conductive foreign matter having a length of 50 μm or more in the flow direction or the width direction of the film present in the film is less than 60 pieces / square meter.
[0015] In every 1×10 6 The number of unstable functional groups of the fluororesin is preferably less than 350 out of the main chain carbon atoms.
[0016] The fluororesin is preferably a tetrafluoroethylene / perfluoro(alkyl vinyl ether) copolymer (PFA) or a tetrafluoroethylene / hexafluoropropylene copolymer (FEP).
[0017] The melt flow rate of the fluororesin at 372° C. and a load of 49 N is preferably 0.1 g / 10 min to 50 g / 10 min.
[0018] The film preferably has an area of 1 square meter or more.
[0019] The conductive foreign matter includes nickel and / or carbide.
[0020] It is preferred that the bonding strength of the film when bonded to a metal foil having a surface roughness Rz of 1.5 μm or less is 0.8 N / mm or more.
[0021] The above-mentioned film is preferably used for a metal-clad laminate.
[0022] The present disclosure also relates to a metal-clad laminate including a metal foil and any one of the above-mentioned fluororesin films as essential layers.
[0023] The metal-clad laminate preferably further comprises a layer other than the metal foil and the fluororesin film.
[0024] The layer other than the metal foil and the fluororesin film is at least one selected from the group consisting of polyimide, liquid crystal polymer, polyphenylene sulfide, cycloolefin polymer, polystyrene, epoxy resin, bismaleimide, polyphenylene oxide, polyphenylene ether and polybutadiene.
[0025] The surface roughness Rz of the metal foil is preferably 1.5 μm or less.
[0026] In the metal-clad laminate, it is preferred that the bonding strength between the metal foil and the fluororesin film is 0.8 N / mm or more.
[0027] The present disclosure also relates to a circuit substrate, characterized by comprising any one of the metal-clad laminates described above.
[0028] Effects of the Invention
[0029] The fluororesin film of the present disclosure is a film with reduced appearance defects and poor adhesion to metal foil and good adhesion to metal foil. DETAILED DESCRIPTION
[0030] Hereinafter, the present invention will be described in detail.
[0031] The present disclosure relates to a film made of a fluororesin, wherein the number of conductive foreign particles having a length of 50 μm or more in the flow direction or the width direction of the film and present on the film surface is less than 60 pieces / square meter.
[0032] In this specification, the flow direction of the film refers to the direction in which the film flows when the film is molded using a film manufacturing device. The width direction refers to the direction perpendicular to the flow direction. The molding of the film includes: a method using melt molding such as extrusion molding; a method using a casting method based on preparing a solution or dispersion containing a fluororesin, applying it to a substrate and drying it.
[0033] The present inventors have found that the presence of conductive foreign matter in a fluororesin film increases the variation in film thickness near the foreign matter, which leads to poor appearance and poor adhesion to metal foil when the film is used for a circuit board.
[0034] It was further discovered that if the number of the above-mentioned conductive foreign matter present on the surface of the film is less than 60 pieces / square meter and the length in the flow direction or the width direction of the film is 50 μm or more, a circuit substrate can be provided that can suppress poor appearance, poor adhesion to metal foil, and low transmission loss.
[0035] In addition, the inventors have confirmed that the conductive foreign matter is metals such as nickel, carbides, etc. Since nickel mainly comes from filters in a film melt extruder used in the film manufacturing process, the use of a nickel-based metal sintered filter cleaned by ultrasonic waves can minimize the amount of metals such as nickel in the film.
[0036] In addition, it is clear that carbides are produced by thermal decomposition of unstable functional groups of fluororesin during extrusion molding, etc. Therefore, the number of unstable functional groups of fluororesin is reduced to suppress the generation of carbides.
[0037] Hereinafter, the present disclosure will be described in more detail.
[0038] The present disclosure relates to a film composed of a fluororesin. It should be noted that the film may contain other resins, rubber, additives, fillers, etc. other than the fluororesin.
[0039] Furthermore, the fluororesin may contain at least one functional group selected from a carbonyl-containing group (e.g., an acid anhydride group, a group having a carbonyl group between carbon atoms of a hydrocarbon group, a carbonate group, a carboxyl group, a haloformyl group, an alkoxycarbonyl group, etc.), a hydroxyl group, an epoxy group, an amide group, an amino group, and an isocyanate group.
[0040] There is no particular limitation on the method for introducing the functional group, and for example, the functional group can be introduced when manufacturing the fluororesin. In this case, the functional group is selected from at least one of the monomers, chain transfer agents and polymerization initiators used in the manufacturing. As the monomer, for example, itaconic anhydride, citraconic anhydride, 5-norbornene-2,3-dicarboxylic anhydride, maleic anhydride, etc. can be cited. As a chain transfer agent, for example, chain transfer agents from methanol, acetic acid, acetic anhydride, methyl acetate, ethylene glycol, propylene glycol, etc. can be cited, and as a polymerization initiator, for example, ammonium persulfate, potassium persulfate, di-n-propyl peroxydicarbonate, diisopropyl peroxycarbonate, tert-butyl peroxyisopropyl carbonate, bis(4-tert-butylcyclohexyl) peroxydicarbonate, di-2-ethylhexyl peroxydicarbonate, etc. can be cited.
[0041] The fluororesin is more preferably a fluororesin that can be melt-molded, and examples thereof include tetrafluoroethylene-perfluoroalkyl vinyl ether copolymer (PFA), a copolymer having a chlorotrifluoroethylene (CTFE) unit (CTFE copolymer), tetrafluoroethylene-hexafluoropropylene copolymer (FEP), tetrafluoroethylene-ethylene copolymer (ETFE), polychlorotrifluoroethylene (PCTFE), chlorotrifluoroethylene-ethylene copolymer (ECTFE), polyvinylidene fluoride (PVDF) and polyvinyl fluoride (PVF), tetrafluoroethylene-hexafluoropropylene-vinylidene fluoride copolymer (THV), tetrafluoroethylene-vinylidene fluoride copolymer, and the like.
[0042] Among these melt-moldable fluororesins, tetrafluoroethylene-perfluoroalkyl vinyl ether copolymers (PFA) and tetrafluoroethylene-hexafluoropropylene copolymers (FEP) are preferred.
[0043] By using the above-mentioned melt-moldable fluororesin, melt molding is possible, so the processing cost can be suppressed compared with the case of using PTFE. Furthermore, the adhesion when bonding with metal foil can be improved.
[0044] The glass transition temperature of the resin constituting the fluororesin film is preferably 40°C or higher. If it is 40°C or higher, for example, when the roll film is stored at room temperature, deformation at ambient temperature is less likely to occur, which is preferred from this point of view, more preferably 60°C or higher, and further preferably 80°C or higher. The upper limit is not particularly limited, but from the viewpoint of adhesiveness, it is preferably 200°C or lower, more preferably 160°C or lower, and further preferably 120°C or lower.
[0045] The melting point of PFA is preferably 180 to 340° C., more preferably 230 to 330° C., and further preferably 280 to 320° C. The melting point is a temperature corresponding to a maximum value in a heat of fusion curve when the temperature is increased at a rate of 10° C. / min using a differential scanning calorimeter [DSC].
[0046] The PFA is not particularly limited, but preferably a copolymer in which the molar ratio of TFE unit to PAVE unit (TFE unit / PAVE unit) is 70 / 30 or more and less than 99.5 / 0.5. A more preferred molar ratio is 70 / 30 or more and 98.9 / 1.1 or less, and a further preferred molar ratio is 80 / 20 or more and 98.5 / 1.5 or less. If the TFE unit is too little, the mechanical properties tend to decrease; if it is too much, the melting point is too high and the moldability tends to decrease.
[0047] The above-mentioned PFA may be a copolymer consisting of only TFE and PAVE, and is also preferably a copolymer in which the monomer unit derived from the monomer copolymerizable with TFE and PAVE is 0.1 mol% to 10 mol%, and the total of TFE unit and PAVE unit is 90 mol% to 99.9 mol%. Examples of monomers copolymerizable with TFE and PAVE include HFP, CZ3Z4=CZ5(CF2) n A vinyl monomer represented by Z6 (wherein Z3, Z4 and Z5 are the same or different and represent a hydrogen atom or a fluorine atom, Z6 represents a hydrogen atom, a fluorine atom or a chlorine atom, and n represents an integer of 2 to 10), and an alkyl perfluorovinyl ether derivative represented by CF2=CF-OCH2-Rf7 (wherein Rf7 represents a perfluoroalkyl group having 1 to 5 carbon atoms). Other copolymerizable monomers include, for example, cyclic hydrocarbon monomers having an anhydride group, and anhydride-based monomers include itaconic anhydride, citraconic anhydride, 5-norbornene-2,3-dicarboxylic anhydride, maleic anhydride, and the like. Anhydride-based monomers may be used alone or in combination of two or more.
[0048] As the above-mentioned FEP, there is no particular limitation, but a copolymer in which the molar ratio of TFE units to HFP units (TFE units / HFP units) is 70 / 30 or more and less than 99 / 1 is preferred. A more preferred molar ratio is 70 / 30 or more and 98.9 / 1.1 or less, and a further preferred molar ratio is 80 / 20 or more and 97 / 3 or less. If the TFE unit is too little, the mechanical properties tend to decrease; if it is too much, the melting point is too high and the moldability tends to decrease. FEP is also preferably a copolymer in which the monomer units from monomers copolymerizable with TFE and HFP are 0.1 mol% to 10 mol%, and the total of TFE units and HFP units is 90 mol% to 99.9 mol%. As monomers copolymerizable with TFE and HFP, alkyl perfluorovinyl ether derivatives can be cited. As other copolymerizable monomers, for example, cyclic hydrocarbon monomers having an acid anhydride group, etc., as acid anhydride monomers, there can be mentioned itaconic anhydride, citraconic anhydride, 5-norbornene-2,3-dicarboxylic anhydride, maleic anhydride, etc. The acid anhydride monomers can be used alone or in combination of two or more.
[0049] The melting point of the FEP is preferably 150 to 320° C., more preferably 200 to 300° C., and even more preferably 240 to 280° C. The melting point is a temperature corresponding to a maximum value in a heat of fusion curve when the temperature is increased at a rate of 10° C. / min using a differential scanning calorimeter [DSC].
[0050] The fluororesin preferably has fewer functional groups, and particularly preferably has fewer unstable functional groups. Such fluororesins include methods for making them by adjusting the conditions during manufacturing (polymerization reaction), methods for reducing the number of unstable functional groups by subjecting the polymerized fluororesin to fluorine gas treatment (fluorination treatment), heat treatment, supercritical gas extraction treatment, etc. Fluorine gas treatment is preferred from the perspective of excellent treatment efficiency and the aspect that a part or all of the unstable functional groups are converted into -CF3 to become stable functional groups.
[0051] If a fluororesin with a reduced number of unstable functional groups is used, the generation of conductive carbides caused by thermal decomposition of the unstable functional groups of the fluororesin can be suppressed during extrusion molding in the film manufacturing process. In addition, it is preferred in terms of reducing the electrostatic loss tangent and reducing the loss of electrical signals.
[0052] The number of unstable functional groups is not particularly limited, and is 6 The number of carbon atoms in the main chain is preferably less than 350, more preferably less than 200, further preferably less than 20, and most preferably less than 10.
[0053] By setting it as such a range, carbides are less likely to be generated during film production, and thus the amount of conductive foreign matter in the film can be suppressed.
[0054] Specific examples of unstable functional groups include -COF, -COOH free (free COOH), -COOH bonded (associated -COOH), hydroxyl (-CH2OH, etc.), -CONH2, -COOR (R=CH3, etc.), -CF2H, -OCOO-R (n-propyl carbonate, etc.), and the like.
[0055] Specifically, the number of unstable functional groups is determined by the following method. First, the fluororesin is melted and compression molded to produce a film with a thickness of 0.25 mm to 0.3 mm. The film is analyzed by Fourier transform infrared spectroscopy to obtain an infrared absorption spectrum of the fluororesin and a differential spectrum from a background spectrum of a completely fluorinated film without functional groups. The number of unstable functional groups per 1×10 6 The number of unstable functional groups in the main chain carbon atoms.
[0056] N=I×K / t(A)
[0057] I: Absorbance
[0058] K: Correction coefficient
[0059] t: film thickness (mm)
[0060] For reference, regarding the unstable functional groups in this specification, the absorption frequency, molar absorption coefficient and correction coefficient are shown in Table 1. In addition, the molar absorption coefficient is determined from the FT-IR measurement data of the low molecular model compound.
[0061] [Table 1]
[0062] Unstable functional groups Absorption frequency (cm-1) Molar absorption coefficient (1 / cm / mol) Correction factor Model compounds -CoF 1883 600 388 <![CDATA[C7F 1F COF]]> -COOH(free) 1815 530 439 <![CDATA[H(CF2)6C0OH]]> -COOH(bonding) 1779 530 439 <![CDATA[H(CF2)6COOH]]> -COOCH3 1795 680 342 <![CDATA[C7F 15 COOCH3<!-- 4 --> ]]> -CONH2 3436 506 460 <![CDATA[C7F 15 CONH2]]> -CH2OH 3648 104 2236 <![CDATA[C7F 15 CH2OH]]> -CF2H 3020 8.8 26485 <![CDATA[H(CF2CF2)3CH2OH]]> -OC(=O)OR 1817 - 1426 -
[0063] The fluorination treatment can be performed by bringing the fluorine-containing compound into contact with the fluorine-containing resin which has not been fluorinated.
[0064] The fluorine-containing compound is not particularly limited, and a fluorine radical source that generates fluorine radicals under fluorination conditions can be cited. As the fluorine radical source, F2 gas, CoF3, AgF2, UF6, OF2, N2F2, CF3OF, fluorinated halogens (e.g., IF5, ClF3), etc. can be cited.
[0065] The fluorine radical source such as the F2 gas may be a fluorine radical source of 100% concentration, but is preferably mixed with an inert gas and diluted to 5% to 50% by mass, more preferably diluted to 15% to 30% by mass. As the inert gas, nitrogen, helium, argon, etc. may be cited, and nitrogen is preferred from an economical aspect.
[0066] The conditions of the fluorination treatment are not particularly limited, and the fluorinated resin in a molten state may be brought into contact with the fluorine-containing compound, but it may be generally carried out at a temperature below the melting point of the fluorinated resin, preferably at 20°C to 220°C, and more preferably at 100°C to 200°C. The fluorination treatment is generally carried out for 1 hour to 30 hours, preferably for 5 hours to 25 hours. The fluorination treatment is preferably a treatment in which the fluorinated resin that has not been subjected to fluorination treatment is brought into contact with fluorine gas (F2 gas).
[0067] In the present specification, the content of each monomer unit constituting the fluororesin can be calculated by appropriately combining NMR, FT-IR, elemental analysis, and fluorescent X-ray analysis according to the types of monomers.
[0068] The fluororesin preferably has a melt flow rate (MFR) of 0.1 to 50 g / 10 min at 372° C. and a load of 49 N, more preferably 0.5 to 40 g / 10 min, and still more preferably 1 to 30 g / 10 min.
[0069] In addition, in this specification, MFR is a value measured according to ASTM D3307 under the above conditions.
[0070] By setting the MFR to the above range, the amount of unstable functional groups is less than 350, the generation of carbides is suppressed, and the reduction of conductive foreign matter can be achieved.
[0071] In addition, when a fluororesin film is produced by extrusion melt molding, the melting temperature is preferably also adjusted, and a temperature range in which the above-mentioned MFR value can be obtained is preferably selected. Specifically, the preferred melting temperature varies depending on the type of resin, the molecular weight of the resin, etc., but it is preferably adjusted to set the temperature in the range of 340°C to 370°C so that the MFR of the resin is within a specified range.
[0072] The fluororesin film of the present disclosure may contain components other than fluororesin. The components that may be contained are not particularly limited, and examples thereof include fillers such as silica particles and short glass fibers, and fluorine-free thermosetting resins / thermoplastic resins.
[0073] The fluororesin-containing composition of the present disclosure may contain spherical silica particles, which improves the fluidity of the resin and facilitates molding even when a large amount of silica is blended.
[0074] The above-mentioned spherical silica particles refer to particles whose shape is close to a true sphere. Specifically, the sphericity is preferably above 0.80, more preferably above 0.85, further preferably above 0.90, and most preferably above 0.95. The sphericity is calculated as follows: a photograph is taken using an SEM, and the area and perimeter of the observed particles are calculated as a value calculated by (sphericity) = {4π×(area) ÷ (perimeter) 2}. The closer to 1, the closer to a true sphere. Specifically, the arithmetic mean value of 100 particles measured using an image processing device (Spectris Co., Ltd.: FPIA-3000) is used.
[0075] For the above-mentioned spherical silica particles, when the volume is integrated from the side with a smaller particle size, preferably D90 / D10 is 2 or more (preferably 2.3 or more, 2.5 or more), and D50 is 10 μm or less. Furthermore, D90 / D50 is preferably 1.5 or more (more preferably 1.6 or more). D50 / D10 is preferably 1.5 or more (more preferably 1.6 or more). Since spherical silica particles with a small particle size may enter the gaps between spherical silica particles with a large particle size, the filling property is excellent and the fluidity can be improved. In particular, as a particle size distribution, it is preferred that the frequency of the side with a smaller particle size is larger than that of a Gaussian curve. The particle size can be measured using a laser diffraction scattering particle size distribution measuring device. In addition, it is preferred to remove coarse particles with a particle size larger than a specified particle size using a filter or the like.
[0076] The water absorption of the spherical silica particles is preferably 1.0% or less, and more preferably 0.5% or less. The water absorption is based on the mass of the silica particles when dried. In the measurement of water absorption, the sample in a dry state is placed at 40°C 80% RH for 1 hour, and the water generated by heating at 200°C is measured using a Karl Fischer moisture meter, and the water absorption is calculated.
[0077] Alternatively, the spherical silica particles may be prepared by heating the fluororesin-containing composition at 600° C. for 30 minutes in an air atmosphere to burn off the fluororesin, taking out the spherical silica particles, and then measuring the above parameters by the above methods.
[0078] The silica powder of the present invention may be surface treated. By previously performing the surface treatment, aggregation of the silica particles can be suppressed, and the silica particles can be well dispersed in the resin composition.
[0079] The surface treatment is not particularly limited, and any known surface treatment can be used. Specifically, for example, treatment with silane coupling agents such as epoxy silane, amino silane, vinyl silane, acrylic silane, hydrophobic alkyl silane, phenyl silane, and fluoroalkyl silane having a reactive functional group, plasma treatment, fluorination treatment, etc. can be cited.
[0080] Examples of the silane coupling agent include epoxysilanes such as γ-glycidoxypropyltriethoxysilane and β-(3,4-epoxycyclohexyl)ethyltrimethoxysilane, aminosilanes such as aminopropyltriethoxysilane and N-phenylaminopropyltrimethoxysilane, vinylsilanes such as vinyltrimethoxysilane, and acrylsilanes such as acryloxytrimethoxysilane.
[0081] The spherical silica can use commercially available silica particles that satisfy the above properties. As commercially available silica particles, for example, Denka fused silica FB grade (manufactured by Denka Co., Ltd.), Denka fused silica SFP grade (manufactured by Denka Co., Ltd.), EXCELICA (manufactured by Tokuyama Co., Ltd.), high-purity synthetic spherical silica ADMAFINE (manufactured by Admatechs Co., Ltd.), ADMANANO (manufactured by Admatechs Co., Ltd.), ADMAFUSE (manufactured by Admatechs Co., Ltd.), etc. can be cited.
[0082] The fluororesin film of the present disclosure needs to have the number of conductive foreign particles having a length of 50 μm or more in the flow direction or the width direction of the film being less than 60 pieces / m 2 .
[0083] The number of the conductive foreign matter is preferably less than 60 pieces / m2, preferably less than 40 pieces / m2, more preferably less than 20 pieces / m2, and further preferably less than 10 pieces / m2.
[0084] The interval between adjacent signal lines of the high-frequency substrate is about 50 μm. It is believed that the presence of conductive foreign matter across the signal lines increases the current when voltage is applied, resulting in a decrease in insulation resistance. Therefore, by reducing the number of conductive foreign matter with a length of 50 μm or more in the flow direction or width direction of the film in the film, poor insulation of the high-frequency substrate can be suppressed, and a circuit substrate with less transmission loss can be obtained.
[0085] In the present disclosure, conductive foreign matter includes metals such as nickel, iron, molybdenum, chromium, aluminum, and copper mixed in during the membrane manufacturing process, and carbides produced by thermal decomposition of unstable functional groups of fluororesins. As described above, nickel is considered to include nickel from filters used in membrane manufacturing, and other metals are considered to come from containers, piping, etc. used in manufacturing.
[0086] In particular, the conductive foreign matter is mainly nickel and carbide, and it is preferred to reduce them. The total number of nickel and carbide present on the film surface with a length of 50 μm or more in the flow direction of the film or the width direction is preferably less than 40 pieces / square meter, more preferably less than 20 pieces / square meter, and further preferably less than 10 pieces / square meter.
[0087] The conductive foreign matter has the same reflectivity in the wavelength range from visible light to near infrared light. Using this property, a material having a reflectivity close to that of a material when irradiated with visible light and near infrared light is defined as a conductive foreign matter.
[0088] In the present disclosure, the number of conductive foreign matter is detected by the following method. That is, a film is inspected using a sheet inspection device (product name, etc.: Super NASP-λ, manufactured by Omron Corporation). The film is passed between a multi-wavelength camera of the sheet inspection device provided in a molding machine and an illumination device irradiating visible light and near-infrared light. At this time, a material having a ratio of reflectivity when irradiating visible light and near-infrared light to a foreign matter, i.e., a metallic degree of 70 or more, is regarded as a conductive foreign matter.
[0089] It should be noted that the fisheyes described in the above-mentioned prior art documents 2 to 4 can be identified as white opaque parts or protrusions during film molding. In particular, in fluororesins, resin components that exist as impurities in fluororesins, such as components with abnormally large molecular weights, components with a large amount of TFE components, or components generated by recombination and cross-linking caused by heat during molding, do not belong to the above-mentioned conductive foreign matter.
[0090] Therefore, even if the number of fisheyes in the film is reduced, the effect of a circuit board with low transmission loss obtained by reducing conductive foreign matter of a specific size cannot be expected.
[0091] The fluororesin resin film disclosed herein preferably has a dielectric loss tangent of less than 0.0015 at 10 GHz. By being within this range, the loss of electrical signals in the circuit can be suppressed to a low level, which is preferred. The dielectric loss tangent is more preferably less than 0.0013, further preferably less than 0.0010, and most preferably less than 0.00050.
[0092] In addition, assuming transmission of signals at higher frequencies or transmission and reception of antennas, the dielectric loss tangent at 40 GHz is preferably less than 0.0015, more preferably less than 0.0013, further preferably less than 0.0010, and most preferably less than 0.00050.
[0093] In order to make the dielectric loss tangent within the above range, it is preferable to use a resin having a small amount of unstable functional groups, and it is more preferable to use a fluorinated fluorine resin.
[0094] The bonding strength of the fluororesin film and the metal foil having a surface roughness Rz of 1.5 μm or less when bonded by vacuum hot pressing under the conditions of a temperature of at least the melting point of the fluororesin and not more than the melting point + 30°C, a pressure of 1.5 MPa to 3.0 MPa, and a time of 300 seconds to 600 seconds is preferably 0.8 N / mm or more, more preferably 0.9 N / mm or more, and still more preferably 1.0 N / mm or more. The bonding strength herein refers to the bonding strength measured under the conditions described in the examples for the laminate bonded under the above conditions.
[0095] The fluororesin film preferably has an adhesive strength of more than 30 N / m when the films are bonded to each other on the same surface at 200° C. for only one side or both sides. With such an adhesive strength, even after the fluororesin film is heat-treated, the film has excellent adhesion when used in combination with various other substrates. The adhesive strength is more preferably more than 50 N / m, and even more preferably more than 100 N / m.
[0096] The thickness of the fluororesin film disclosed herein is preferably 2.5 to 1000 μm, more preferably 5 to 500 μm, and even more preferably 12.5 to 150 μm. The thickness can be selected in consideration of the balance between the electrical properties and the linear expansion coefficient of the laminate.
[0097] The area of the fluororesin film of the present disclosure is preferably 1 square meter or more, and is particularly preferably a long film of 100 m or more.
[0098] (Method for producing fluororesin film)
[0099] Hereinafter, an example of the method for producing the fluororesin film of the present disclosure will be described in detail. It should be noted that the fluororesin film of the present disclosure is not limited to the one produced by the following production method.
[0100] The fluororesin film disclosed in the present invention is not particularly limited to the molding method when it is made into a film state, and examples thereof include a method of melt molding such as extrusion molding; a method of using a casting method based on preparing a solution or dispersion containing a fluororesin, applying it to a substrate and drying it; etc. Furthermore, the film may be stretched by a uniaxial stretching method or a biaxial stretching method, or may be an unstretched film.
[0101] In the case of the above-mentioned melt molding, a nickel-based corrosion-resistant filter composed of nickel metal, a nickel alloy such as Hastelloy, Kormonoy, or monel is generally used as a filter in a melt extruder or the like used in film production.
[0102] In the present disclosure, as a filter, a sintered filter is preferred from the aspects of filtration accuracy and filter life. By using a sintered filter, it is possible to remove small foreign matter such as relatively small carbides or metal pieces with a length of about 50 μm in the flow direction or width direction of the above-mentioned membrane without meshes between the screens.
[0103] Examples of such filters include filters obtained by laminating a plurality of nickel or nickel alloy plain woven metal meshes and sintering them to form an integrated structure, and sintered filter media obtained by sintering metal long fibers or metal powders.
[0104] In addition, metal powder, burrs of the metal mesh, and other metals attached to the filter may exist in the filter due to metal processing. For example, burrs may be generated on the metal mesh of a sintered filter when the filter is sintered. Such metal powder and burrs may be separated from the filter during membrane manufacturing and mixed into the fluororesin.
[0105] Therefore, in the present disclosure, it is preferred to use a filter that has been dusted and cleaned. In order to remove dust and clean the filter, immersion cleaning can be performed by immersing the filter in an immersion tank storing a cleaning solution or pure water, spray cleaning can be performed by spraying a cleaning solution or pure water at a high pressure onto the metal filter, or a cleaning method that combines these immersion cleaning and spray cleaning. In addition, the filter can also be ultrasonically cleaned with a cleaning solution or pure water. Through these cleaning processes, nickel and the like that are detached during membrane manufacturing can be reduced.
[0106] In the present disclosure, it is preferred to use a filter that has been cleaned by ultrasonic waves. The method of ultrasonic cleaning is not particularly limited and can be performed by a conventional method. For example, the treatment time can generally be about 5 minutes to 1 hour.
[0107] The fluororesin film obtained by such a method is preferably subjected to surface treatment and annealing treatment on one or both sides under appropriate conditions.
[0108] By performing surface treatment and annealing treatment, a fluororesin film can be obtained in which the oxygen ratio is 1.35 atomic % or more when the surface state of one or both sides is measured by ESCA after heat treatment at 180°C × 3 minutes, and the absolute value of the dimensional change rate of MD and TD before and after heat treatment is 2.0% or less when measured after cooling to 25°C after heat treatment at 180°C × 10 minutes. Therefore, it is preferred.
[0109] The effect of the surface treatment of the fluororesin film for improving the adhesion tends to be reduced by heating. It is speculated that this is because the oxygen atoms on the surface are detached by heating, and the amount of oxygen atoms on the surface is reduced. In the lamination process, in order to improve productivity, lamination is sometimes performed after preheating at a temperature above the glass transition temperature and below the melting point. In this way, in order to ensure sufficient adhesion when the fluororesin film subjected to the thermal history is bonded to the metal foil, it is preferred that the oxygen atom ratio of the surface bonded to the metal foil is measured by a scanning X-ray photoelectron spectroscopy analyzer (XPS / ESCA) after the film is heat treated at 180°C for 3 minutes to be 1.35 atomic % or more.
[0110] The specific method of the surface modification is not particularly limited, and the surface modification can be performed by any known method.
[0111] The surface modification of the fluororesin film can be carried out by a discharge treatment based on corona discharge treatment, glow discharge treatment, plasma discharge treatment, sputtering treatment, etc., which has been carried out in the past. For example, in addition to controlling the surface free energy by introducing oxygen, nitrogen, hydrogen, etc. into the discharge atmosphere, the surface to be modified is exposed to an atmosphere of an inert gas containing an organic compound as an inert gas containing an organic compound, and a high-frequency voltage is applied between electrodes to generate a discharge, thereby generating active species on the surface, and then introducing functional groups of organic compounds or graft-polymerized organic compounds, thereby surface modification can be carried out. Examples of the above-mentioned inert gas include nitrogen, helium, argon, etc.
[0112] Examples of the organic compound in the above-mentioned inert gas containing organic compounds include polymerizable or non-polymerizable organic compounds containing oxygen atoms, such as vinyl esters such as vinyl acetate and vinyl formate; acrylic esters such as glycidyl methacrylate; ethers such as vinyl ethyl ether, vinyl methyl ether, and glycidyl methyl ether; carboxylic acids such as acetic acid and formic acid; alcohols such as methanol, ethanol, phenol, and ethylene glycol; ketones such as acetone and methyl ethyl ketone; carboxylic acid esters such as ethyl acetate and ethyl formate; acrylic acids such as acrylic acid and methacrylic acid, etc. Among these, vinyl esters, acrylic esters, and ketones are preferred, and vinyl acetate and glycidyl methacrylate are particularly preferred, from the perspective of the surface being less likely to be deactivated after modification, that is, having a long life, and being easy to handle.
[0113] The concentration of the organic compound in the above-mentioned inert gas containing organic compounds varies depending on the type of the organic compound, the type of fluororesin to be surface-modified, etc., and is usually 0.1 volume % to 3.0 volume %, preferably 0.1 volume % to 1.0 volume %, more preferably 0.15 volume % to 1.0 volume %, and further preferably 0.30 volume % to 1.0 volume %. The discharge conditions can be appropriately selected according to the degree of surface modification as the target, the type of fluororesin, the type or concentration of the organic compound, etc. Usually, when the discharge amount is 50W·min / m 2 ~1500W·min / m 2 , preferably 70W·min / m 2 Above 1400W·min / m 2The discharge treatment is carried out within the following range. The treatment temperature can be carried out at any temperature in the range of more than 0°C and less than 100°C. Due to concerns about elongation and wrinkles of the film, it is preferably below 80°C. Regarding the degree of surface modification, considering that the adhesion of the surface is reduced due to heat during post-processing, the presence ratio of oxygen element when observed by ESCA is more than 2.6%, preferably more than 2.8%, more preferably more than 3.0%, and further preferably more than 3.5%. There is no particular provision on the upper limit, but in view of the impact on productivity and other physical properties, it is preferably less than 25.0%. There is no particular provision on the presence ratio of nitrogen element, but it is preferably more than 0.1%. In addition, the thickness of one fluororesin film is preferably 2.5μm to 1000μm, more preferably 5μm to 500μm, and further preferably 7μm to 150μm.
[0114] In the manufacture of the fluororesin film disclosed herein, it is preferred to perform annealing after the above-mentioned surface treatment. In addition, sometimes heat treatment is performed in the process of laminating the film with other materials such as metal foil. Therefore, by undergoing these heat treatments, the amount of oxygen on the surface of the fluororesin film is reduced. Thus, it is preferred to perform surface modification under the condition of obtaining sufficient surface oxygen at the moment when the fluororesin film is actually attached to other materials such as metal foil.
[0115] (Annealing treatment)
[0116] The annealing treatment can be performed by heat treatment. The heat treatment can be performed, for example, by passing the roll-to-roll through a heating furnace.
[0117] The annealing temperature is preferably above the glass transition temperature -20 ° C and below the melting point, more preferably above the glass transition temperature and below the melting point -20 ° C, and further preferably above the glass transition temperature and below the melting point -60 ° C. The annealing time is not particularly limited, for example, it can be appropriately adjusted in 0.5 minutes to 60 minutes. In addition, if the film after passing through the annealing furnace contacts the roller of the winding device at high temperature, it is easy to cause the film to deform (undulate) due to the thermal contraction caused by the temperature change. In order to prevent this situation, it is also possible to pass through the cooling area after the high temperature annealing area, thereby cooling the film and winding it up using the winding device. There is no particular limitation as the cooling method, and it can be cooled by cold air, cooling rollers, etc., and the film temperature is preferably set to be lower than the glass transition temperature.
[0118] When heating in the roll-to-roll manner, the tension can be appropriately adjusted according to the film thickness, set temperature, etc., and is preferably 20 N / m or less. By heating under such conditions, internal stress can be fully relaxed and dimensional changes will not occur, which is preferred.
[0119] The order of the surface treatment and annealing treatment is not particularly limited, and the number of times each process is performed is not limited to one time, and it can also be performed more than two times. Since tension is applied in the surface treatment process, it is preferred to perform annealing after the surface treatment from the perspective of controlling the thermal shrinkage rate. In addition, it is also possible to cut into a specified width and length before or after these treatments. In this case, it is preferred to adjust the tension in a way that the film does not stretch.
[0120] The fluororesin film disclosed herein can be used as a sheet for a printed wiring board by being laminated with other base materials.
[0121] Examples of the other substrates include metal foils and resin films other than fluororesins.
[0122] The present disclosure also relates to a metal-coated laminate, characterized in that a metal foil is bonded to one or both sides of the above-mentioned fluororesin film. As described above, the film containing fluororesin disclosed in the present disclosure improves the bonding processing yield with the substrate, and also has good adhesion. The Rz of the above-mentioned metal foil is preferably less than 1.5 μm. That is, the adhesion of the fluororesin film disclosed in the present disclosure to a metal foil with high smoothness and an Rz of less than 1.5 μm is also excellent. Furthermore, as long as at least the surface of the metal foil bonded to the above-mentioned fluororesin film is less than 1.5 μm, the Rz value of the other surface is not particularly limited.
[0123] The Rz of the metal foil was measured using a color 3D laser microscope VK-9700 manufactured by KEYENCE Corporation at 200 μm. 2 The value obtained by calculating the maximum height Rz of the range.
[0124] The thickness of the metal foil is not particularly limited, but is preferably in the range of 1 μm to 100 μm, more preferably in the range of 5 μm to 50 μm, and even more preferably in the range of 9 μm to 35 μm.
[0125] The metal foil is preferably copper foil.
[0126] The copper foil is not particularly limited, and specific examples thereof include rolled copper foil and electrolytic copper foil.
[0127] The copper foil having an Rz of 1.5 μm or less is not particularly limited, and commercially available copper foil can be used. Examples of commercially available copper foil having an Rz of 1.5 μm or less include electrolytic copper foil CF-T9DA-SV-18 (thickness 18 μm / Rz 0.85 μm) (manufactured by Fukuda Metal Foil Co., Ltd.).
[0128] The metal foil may be subjected to a surface treatment in order to improve the bonding strength with the fluororesin film of the present disclosure.
[0129] The surface treatment is not particularly limited, and is silane coupling treatment, plasma treatment, corona treatment, UV treatment, electron beam treatment, etc. The reactive functional group of the silane coupling agent is not particularly limited. From the aspect of adhesion to the resin substrate, it is preferred to have at least one selected from amino, (meth) acryloyl, mercapto and epoxy groups at the terminal. In addition, the hydrolyzable group is not particularly limited, and alkoxy groups such as methoxy and ethoxy can be cited. The metal foil used in the present disclosure can be formed with a rust-proof layer (oxide film such as chromate, etc.), a heat-resistant layer, etc.
[0130] The surface-treated metal foil having the surface-treated layer formed of the above-mentioned silane compound on the surface of the metal foil can be produced by preparing a solution containing the silane compound and then surface-treating the metal foil with the solution.
[0131] The metal foil may have a roughening treatment layer on its surface in order to improve adhesion to the resin substrate.
[0132] It should be noted that, if the roughening treatment may reduce the performance required by the present disclosure, the roughening particles electrodeposited on the surface of the metal foil may be reduced as needed, or the roughening treatment may not be performed.
[0133] From the perspective of improving various properties, one or more layers selected from the group consisting of a heat-resistant treatment layer, a rust-proof treatment layer, and a chromate treatment layer may be provided between the metal foil and the surface treatment layer. These layers may be a single layer or multiple layers.
[0134] In the above-mentioned laminate, the bonding strength between the metal foil and the fluororesin film is preferably 0.8N / mm or more. By applying the above-mentioned method, such bonding strength can be achieved. By making the bonding strength 0.9N / mm or more, and further 1.0N / mm or more, it can be suitable for use as a metal-coated laminate and a circuit substrate. It should be noted that the bonding strength herein refers to the bonding strength measured under the conditions described in the embodiments. In addition, in the case of a laminate in which the metal foil is bonded to the surface-treated surface of the fluororesin film that has been surface-treated on only one side, in order to improve the adhesion between the laminate and other materials, the surface of the fluororesin film that has not been surface-treated can also be subjected to surface modification.
[0135] The present disclosure also relates to a laminated body characterized by comprising a metal foil layer, the above-mentioned fluororesin film, and a substrate layer. The substrate layer is not particularly limited, but preferably comprises a cloth layer composed of glass fiber and a resin film layer.
[0136] The above-mentioned cloth layer composed of glass fibers is a layer composed of glass cloth, glass nonwoven fabric, or the like.
[0137] As glass cloth, commercially available glass cloth can be used. In order to improve the affinity with fluororesin, it is preferably treated with a silane coupling agent. As the material of the glass cloth, E glass, C glass, A glass, S glass, D glass, NE glass, low dielectric constant glass, etc. can be cited. From the perspective of easy availability, E glass, S glass, and NE glass are preferred. As for the weaving method of the fiber, it can be plain or twill. The thickness of the glass cloth is usually 5μm to 90μm, preferably 10μm to 75μm. It is preferred to use glass cloth thinner than the fluororesin film used.
[0138] The laminate can use glass nonwoven fabric as the cloth layer composed of glass fiber. Glass nonwoven fabric is a material formed by bonding short glass fibers with a small amount of binder compound (resin or inorganic substance), or a material that maintains its shape by winding glass short fibers without using a binder compound, and commercial products can be used. The diameter of the glass short fibers is preferably 0.5 μm to 30 μm, and the fiber length is preferably 5 mm to 30 mm. As specific examples of binder compounds, resins such as epoxy resins, acrylic resins, cellulose, polyvinyl alcohol, and fluororesins, or inorganic substances such as silica compounds can be cited. The amount of binder compound used is usually 3% to 15% by mass relative to the glass short fibers. As the material of the glass short fibers, E glass, C glass, A glass, S glass, D glass, NE glass, low dielectric constant glass, etc. can be cited. The thickness of the glass nonwoven fabric is usually 50 μm to 1000 μm, preferably 100 μm to 900 μm. It should be noted that the thickness of the glass nonwoven fabric in the present application refers to the value measured using a digital gauge DG-925 (load 110 g, surface diameter 10 mm) manufactured by Ono Sakuki Co., Ltd. in accordance with JIS P8118: 1998. The glass nonwoven fabric may be treated with a silane coupling agent to improve affinity with fluororesin.
[0139] Since the porosity of most glass nonwoven fabrics is 80% or more, which is very high, it is preferable to use a glass nonwoven fabric thicker than the sheet made of fluororesin and compress it by pressure.
[0140] The cloth layer composed of the glass fiber may be a layer formed by laminating glass cloth and glass nonwoven fabric. In this way, the properties of each other are combined to obtain appropriate properties.
[0141] The cloth layer composed of the glass fiber may be in the state of a prepreg impregnated with a resin.
[0142] In the above-mentioned laminate, the cloth layer composed of glass fibers and the fluororesin film may be bonded at the interface, or the fluororesin film may be partially or entirely impregnated into the cloth layer composed of glass fibers.
[0143] In addition, a fluororesin composition may be impregnated into a cloth made of glass fiber to prepare a prepreg. The prepreg thus obtained may be further laminated with the fluororesin film disclosed herein. In this case, the fluororesin composition used in preparing the prepreg is not particularly limited, and the fluororesin film disclosed herein may also be used.
[0144] As the resin film used as the substrate layer, a heat-resistant resin film and a thermosetting resin film are preferred. Examples of the heat-resistant resin film include polyimide, liquid crystal polymer, polyphenylene sulfide, cycloolefin polymer, polystyrene, etc. Examples of the thermosetting resin include thermosetting resins including epoxy resins, bismaleimide, polyphenylene oxide, polyphenylene ether, polybutadiene, etc.
[0145] The heat-resistant resin film and the thermosetting resin film may contain reinforcing fibers. The reinforcing fibers are not particularly limited, but are preferably glass cloth, and particularly low dielectric constant reinforcing fibers.
[0146] The dielectric properties, linear expansion coefficient, water absorption and other properties of the heat-resistant resin film and the thermosetting resin film are not particularly limited. For example, the dielectric constant at 20 GHz is preferably 3.8 or less, more preferably 3.4 or less, and further preferably 3.0 or less. The dielectric loss tangent at 20 GHz is preferably 0.0030 or less, more preferably 0.0025 or less, and further preferably 0.0020 or less. The linear expansion coefficient is preferably 100 ppm / °C or less, more preferably 70 ppm / °C or less, further preferably 40 ppm / °C or less, and most preferably 20 ppm / °C or less. The water absorption is preferably 1.0% or less, more preferably 0.5% or less, and further preferably 0.1% or less.
[0147] The fluororesin film disclosed herein can be used in a laminate having a metal foil layer, a base material layer, and the fluororesin film.
[0148] The method of laminating the metal foil, the base material layer, and the fluororesin film is not particularly limited, and examples thereof include the following two methods.
[0149] (i) A method of laminating a metal foil, a base material layer, and a preformed fluororesin film by a roll-to-roll process and applying pressure under heating with a press.
[0150] (ii) A method of producing a laminate in which a fluororesin film is bonded to one surface of a metal foil, and laminating the laminate on a base material layer by applying pressure under heating.
[0151] When the metal foil, substrate layer and fluororesin film are laminated by the method (i) above, in order to improve the adhesion of each layer, at least one surface of at least one layer among the metal foil, substrate layer and fluororesin film may be surface treated and bonded to the other layers.
[0152] Furthermore, in order to improve the adhesiveness, the surface treated surface of the metal foil, the base material layer or the fluororesin film may be further treated with a coupling agent or the like.
[0153] Alternatively, an adhesive layer may be provided between these layers regardless of the presence or absence of a previous surface treatment.
[0154] In addition, a rust-proof layer (for example, an oxide film such as chromate) or a heat-resistant layer may be formed on the surface of the metal foil.
[0155] When a laminate having a fluororesin film bonded to one side of a metal foil is produced by the method (ii) above, one or more surfaces of at least one of the metal foil and the fluororesin film may be surface treated before bonding in order to improve the adhesion of the layers.
[0156] Furthermore, in order to improve the adhesiveness, the surface treated surface of the metal foil or the fluororesin film may be further treated with a coupling agent or the like.
[0157] Alternatively, an adhesive layer may be provided between these layers regardless of the presence or absence of a previous surface treatment.
[0158] Furthermore, before or after lamination of the laminate in which the fluororesin film is bonded to one side of the metal foil, the surface of the fluororesin film on which the substrate layer is laminated may be surface treated to improve the adhesion between the fluororesin film and the substrate layer.
[0159] In order to obtain the same effect, the base material layer may be subjected to surface treatment.
[0160] Furthermore, in order to improve the adhesiveness, the surface treated surface of the fluororesin film or the substrate layer may be further treated with a coupling agent or the like.
[0161] Alternatively, an adhesive layer may be provided between these layers regardless of the presence or absence of a previous surface treatment.
[0162] In addition, a rust-proof layer (for example, an oxide film such as chromate) or a heat-resistant layer may be formed on the surface of the metal foil.
[0163] In these methods, when a metal-coated laminate including a fluororesin film and a metal foil is laminated with a base layer such as a cloth layer composed of glass fiber or a resin film layer, the laminate can be laminated by bonding the fluororesin film layer side of the metal-coated laminate to the base layer. In this case, a laminate in which the fluororesin film layer side of the metal-coated laminate is subjected to a surface treatment before lamination to improve the bonding performance can be used. The surface treatment here is not particularly limited, and the above-mentioned plasma treatment and the like can be cited.
[0164] In the laminate, the lamination order of the metal foil layer, the base material layer and the fluororesin film and the production method are not particularly limited, and the laminate can be formed into a layer structure according to the purpose.
[0165] Specific examples of the above-mentioned stacking sequence include a stacking sequence consisting of substrate layer / fluororesin film / metal foil layer, a stacking sequence consisting of metal foil layer / fluororesin film / substrate layer / fluororesin film / metal foil layer, and a stacking sequence consisting of metal foil layer / substrate layer / fluororesin film / substrate layer / metal foil layer.
[0166] In addition, other layers may be provided as required.
[0167] In addition, as the metal foil in the above-mentioned laminate, the same metal foil as the metal foil explained in detail in the above-mentioned laminate with fluororesin films can be used.
[0168] When obtaining the structure of the above-mentioned laminate, the fluororesin film disclosed in the present invention is used by bonding metal foil on one side or both sides. As mentioned above, the fluororesin film disclosed in the present invention has excellent adhesion. Therefore, it also has excellent adhesion to metal foil with high smoothness and Rz of less than 1.5 μm. The bonding strength between the metal foil and the fluororesin film is preferably 0.8 N / mm or more. By setting the bonding strength to 0.9 N / mm or more and further to 1.0 N / mm or more, it can be suitable for use as a metal-coated laminate and a circuit substrate. It should be noted that the bonding strength here refers to the bonding strength measured under the conditions described in the examples.
[0169] In order to ensure the adhesion to the insulating layer, the metal foil used in the circuit substrate has been given a certain degree of concavity and convexity on the surface. However, if the metal foil has concavity and convexity on the surface in high-frequency applications, it will cause loss of electrical signals, so it is not preferred. The above-mentioned laminate can obtain appropriate adhesion even for the metal foil with high smoothness, and becomes a laminate suitable for use as a circuit substrate.
[0170] The fluororesin film disclosed in the present invention has the effect of producing few defects during lamination and also being able to obtain good adhesion to metal foil. Since it has adhesion to metal foil with high smoothness such as Rz of 1.5 μm or less, it can also provide a laminate that can be suitable for use in metal-clad laminates, circuit substrates, flat cables, cover layers, etc.
[0171] In the present disclosure, the high-frequency circuit is not only composed of a circuit that transmits only a high-frequency signal, but also includes a circuit that has a transmission path that converts a high-frequency signal into a low-frequency signal and outputs the generated low-frequency signal to the outside, a transmission path for supplying power to drive a high-frequency corresponding component, and other transmission paths that transmit signals other than high-frequency signals, etc., all provided on the same plane. In addition, it can also be used as a circuit substrate for an antenna, a filter, etc.
[0172] Example
[0173] The present disclosure is specifically described below based on examples. However, the present invention is not limited to the following examples. In the following examples, the ratio is expressed as a molar ratio.
[0174] [Fluororesin]
[0175] PFA1: TFE / PPVE copolymer, composition (molar ratio): TFE / PPVE=98.6 / 1.4, MFR 15.2 g / 10 min, melting point 309.5°C, glass transition temperature 93°C, film formation, number of unstable functional groups after surface treatment: 1×10 6 The number of carbon atoms in the main chain is 324
[0176] [Fluororesin]
[0177] PFA2: TFE / PPVE copolymer, composition (molar ratio): TFE / PPVE=97.7 / 2.3, MFR 14.6 g / 10 min, melting point 300.9°C, glass transition temperature 93°C, film formation, number of unstable functional groups after surface treatment: 1×10 6 The number of carbon atoms in the main chain is 192
[0178] [Fluororesin]
[0179] PFA3: fluorinated TFE / PPVE copolymer, composition (molar ratio): TFE / PPVE=97.7 / 2.3, MFR 15.0 g / 10 min, melting point 300.9°C, glass transition temperature 93°C, film formation, number of unstable functional groups after surface treatment: 1×10 6 The number of carbon atoms in the main chain is 8
[0180] [Fluororesin]
[0181] PFA4: TFE / PPVE copolymer, composition (molar ratio): TFE / PPVE=97.2 / 2.8, MFR 64 g / 10 min, melting point 284°C, glass transition temperature 90°C, film formation, number of unstable functional groups after surface treatment: 1×10 6 The number of carbon atoms in the main chain is 507
[0182] (Polymer composition)
[0183] The determination was carried out by 19F-NMR analysis.
[0184] (Melting Point)
[0185] The temperature was raised at a rate of 10°C / min using a DSC apparatus and the result was calculated from the melting peak during measurement.
[0186] (Glass transition temperature)
[0187] The tan δ peak was calculated from the measurement using a solid dynamic viscoelasticity apparatus (DMA) at a frequency of 10 Hz, a strain of 0.1%, and a temperature increase rate of 5°C / min.
[0188] (Melt flow rate (MFR)
[0189] The measurement was performed according to ASTM D3307 at a temperature of 372°C and a load of 5.0 kg.
[0190] (Thickness of fluororesin film)
[0191] The measurement was performed using a micrometer.
[0192] (Number of unstable functional groups)
[0193] The analysis was performed using FT-IR Spectrometer 1760X (manufactured by Perkin-Elmer).
[0194] (ESCA analysis of fluororesin film surface)
[0195] The measurement was performed using a scanning X-ray photoelectron spectroscopy analyzer (XPS / ESCA) PHI5000VersaProbeII (ULVAC-PHI Co., Ltd.).
[0196] (Surface roughness of copper foil)
[0197] The catalog value of electrolytic copper foil CF-T9DA-SV-18 (thickness 18 μm / Rz 0.85 μm) (manufactured by Fukuda Metal Foil & Powder Co., Ltd.) was adopted.
[0198] (Bond strength between copper foil and fluororesin film)
[0199] A fluororesin film which was not preheated or was preheated at a temperature above the glass transition temperature and below the melting point was used, and copper foil / fluororesin film / copper foil were stacked in this order. An aluminum plate was attached to one side of the laminate produced by vacuum hot pressing with an adhesive tape. A 10 mm wide copper foil was grasped and stretched at a speed of 50 mm per minute in a direction of 90° relative to the plane of the laminate using a Tensilon universal testing machine (manufactured by Shimadzu Corporation) to measure the peel strength of the copper foil, and the obtained value was used as the bonding strength.
[0200] (Measurement of the number of conductive foreign particles)
[0201] Determination of the number of conductive foreign particles
[0202] The number of conductive foreign matter is detected by the following method. That is, the film is inspected using a sheet inspection device (product name, etc.: SuperNASP-λ, manufactured by Omron Corporation). The film is passed between a multi-wavelength camera provided in the inspection device of the molding machine and an illumination device irradiating visible light and near-infrared light. At this time, a material having a ratio of reflectivity when irradiating visible light and near-infrared light, i.e., a metallic degree of 70 or more, is regarded as a conductive foreign matter.
[0203] Nickel: Metal content is 88-92
[0204] Carbide: Metallicity is 95-100
[0205] Other conductive foreign matter: Metallic degree 70 or above and outside the above range
[0206] The number of conductive foreign particles having a length in the flow direction or the width direction of the film of 50 μm or more was detected.
[0207] (Appearance inspection)
[0208] Visual observation 1m 2 The foreign matter in the film was counted using a magnifying glass. The result of the confirmation was that every 1m 2 When the number is less than 10, it is indicated as ◎, when the number is 10 or more and less than 60, it is indicated as ○, and when the number is 60 or more, it is indicated as ×. It should be noted that the black foreign matter that can be visually confirmed is regarded as all conductive foreign matter including nickel and carbide.
[0209] (Evaluation of bonding yield)
[0210] A fluororesin film that has not been preheated or has been preheated above the glass transition temperature and below the melting point is cut into a size of 25 cm × 40 cm, overlapped in the order of copper foil / fluororesin film, and made by vacuum hot pressing. The film bonded to the copper foil of the laminate is visually judged, and foreign matter confirmed from the film surface side is observed using a differential interference microscope (product name: LV100ND, manufactured by Nikon). As conductive foreign matter, those that appear darker near the foreign matter are considered carbides, and those that confirm a metallic luster are considered metal foreign matter. Fisheyes that only confirm bumps are considered non-conductive foreign matter.
[0211] In an area of 25 cm×40 cm, when the number of protrusions from the conductive foreign matter was 1 or less, it was rated as ◎; when the number was 2 or more and 6 or less, it was rated as ○; and when the number was 7 or more, it was rated as ×.
[0212] <Example 1>
[0213] [Method for producing film]
[0214] The PFA1 pellets were put into an extruder at 360°C, in which an ultrasonically cleaned nickel filter with multiple overlapping meshes of #300 or larger was inserted between the screw and the die. The film was extruded from a 1700 mm wide T-die, pulled to a metal cooling roller, and then wound on a winding core to form a 1300 mm wide, 50 μm thick roll film.
[0215] During the film formation, an inspection for conductive foreign matter is performed.
[0216] [Surface treatment of film]
[0217] Next, both sides of the obtained long roll film were subjected to surface treatment (while nitrogen containing 0.50 volume % of vinyl acetate was flowing near the discharge electrode and the roll-shaped ground electrode of the corona discharge device, the film was continuously passed along the roll-shaped ground electrode at a discharge rate of 1324 W·min / m 2 Both sides of the film are subjected to corona discharge treatment), and the surface-treated long strip film is wound into a roll.
[0218] The obtained film was inspected for appearance.
[0219] [Lamination with copper foil]
[0220] The electrolytic copper foil CF-T9DA-SV-18 (thickness 18 μm / Rz 0.85 μm) (manufactured by Fukuda Metal Foil Powder Industry Co., Ltd.) was overlapped in such a manner that the same surface as the surface treated with the fluororesin film was in contact with it, and hot pressing was performed using a vacuum hot press machine (model: MKP-1000HVWH-S7 / manufactured by Mikado Technos Co., Ltd.) at a pressing temperature of 320°C, a preheating time of 60 seconds, a pressure of 1.5 MPa, and a pressing time of 300 seconds to bond them together to obtain a bonded product with a size of 25 cm×40 cm.
[0221] Bonding was performed with a layer structure of copper foil / fluororesin film, and the yield was evaluated. Similarly, bonding was performed with a layer structure of copper foil / fluororesin film / copper foil, and the bonding strength was measured.
[0222] <Example 2>
[0223] A film having a thickness of 25 μm was produced in the same manner as in Example 1. Inspection of conductive foreign matter during film production, inspection of the appearance of the film, evaluation of the yield after bonding, and measurement of the bonding strength were performed.
[0224] <Example 3>
[0225] A film having a thickness of 12.5 μm was produced in the same manner as in Example 1. Inspection of conductive foreign matter during film production, inspection of the appearance of the film, evaluation of the yield after bonding, and measurement of the bonding strength were performed.
[0226] <Example 4>
[0227] A film having a thickness of 50 μm was produced in the same manner as in Example 1 except that PFA2 was used. Inspection of conductive foreign matter during film production, inspection of the appearance of the film, evaluation of the yield after bonding, and measurement of the bonding strength were performed.
[0228] <Example 5>
[0229] A film having a thickness of 25 μm was produced in the same manner as in Example 4. Inspection of conductive foreign matter during film production, inspection of the appearance of the film, evaluation of the yield after bonding, and measurement of the bonding strength were performed.
[0230] <Example 6>
[0231] A film having a thickness of 12.5 μm was produced in the same manner as in Example 4. Inspection of conductive foreign matter during film production, inspection of film appearance, evaluation of yield after bonding, and measurement of bonding strength were performed.
[0232] <Example 7>
[0233] A film having a thickness of 50 μm was produced in the same manner as in Example 1 except that PFA3 was used. Inspection of conductive foreign matter during film production, inspection of the appearance of the film, evaluation of the yield after bonding, and measurement of the bonding strength were performed.
[0234] <Example 8>
[0235] A film having a thickness of 25 μm was produced in the same manner as in Example 7. Inspection of conductive foreign matter during film production, inspection of the appearance of the film, evaluation of the yield after bonding, and measurement of the bonding strength were performed.
[0236] <Example 9>
[0237] A film having a thickness of 12.5 μm was produced in the same manner as in Example 7. Inspection of conductive foreign matter during film production, inspection of film appearance, evaluation of yield after bonding, and measurement of bonding strength were performed.
[0238] <Example 10>
[0239] The PFA1 pellets were put into an extruder at 360°C, in which a nickel filter with multiple overlapping meshes of #300 or larger, which had been sintered and ultrasonically cleaned, was inserted between the screw and the die. The film was extruded from a 1700 mm wide T-die, pulled to a metal cooling roll, and then wound on a winding core to form a 1300 mm wide, 50 μm thick roll film.
[0240] In the same manner as in Example 1, inspection of conductive foreign matter during film formation, inspection of film appearance, evaluation of yield after bonding, and measurement of bonding strength were performed.
[0241] <Example 11>
[0242] A film having a thickness of 25 μm was produced in the same manner as in Example 10. Inspection of conductive foreign matter during film production, inspection of the appearance of the film, evaluation of the yield after bonding, and measurement of the bonding strength were performed.
[0243] <Example 12>
[0244] A film having a thickness of 12.5 μm was produced in the same manner as in Example 10. Inspection of conductive foreign matter during film production, inspection of film appearance, evaluation of yield after bonding, and measurement of bonding strength were performed.
[0245] <Example 13>
[0246] A film having a thickness of 50 μm was produced in the same manner as in Example 10 except that PFA2 was used. Inspection of conductive foreign matter during film production, inspection of the film appearance, evaluation of the yield after bonding, and measurement of the bonding strength were performed.
[0247] <Example 14>
[0248] A film having a thickness of 25 μm was produced in the same manner as in Example 13. Inspection of conductive foreign matter during film production, inspection of film appearance, evaluation of yield after bonding, and measurement of bonding strength were performed.
[0249] <Example 15>
[0250] A film having a thickness of 12.5 μm was produced in the same manner as in Example 13. Inspection of conductive foreign matter during film production, inspection of film appearance, evaluation of yield after bonding, and measurement of bonding strength were performed.
[0251] <Example 16>
[0252] A film having a thickness of 50 μm was produced in the same manner as in Example 10 except that PFA3 was used. Inspection of conductive foreign matter during film production, inspection of the film appearance, evaluation of the yield after bonding, and measurement of the bonding strength were performed.
[0253] <Example 17>
[0254] A film having a thickness of 25 μm was produced in the same manner as in Example 16. Inspection of conductive foreign matter during film production, inspection of the appearance of the film, evaluation of the yield after bonding, and measurement of the bonding strength were performed.
[0255] <Example 18>
[0256] A film having a thickness of 12.5 μm was produced in the same manner as in Example 16. Inspection of conductive foreign matter during film production, inspection of film appearance, evaluation of yield after bonding, and measurement of bonding strength were performed.
[0257] <Comparative Example 1>
[0258] PFA4 pellets were put into an extruder at 360°C, in which a nickel filter with multiple #300 or larger unwashed and sintered meshes was inserted between the screw and the die. The film was extruded from a 1700 mm wide T-die, pulled to a metal cooling roll, and then wound on a winding core to form a 1300 mm wide, 50 μm thick roll film.
[0259] In the same manner as in Example 1, inspection of conductive foreign matter during film formation, inspection of film appearance, evaluation of yield after bonding, and measurement of bonding strength were performed.
[0260] <Comparative Example 2>
[0261] A film having a thickness of 25 μm was produced in the same manner as in Comparative Example 1. Inspection of conductive foreign matter during film production, inspection of film appearance, evaluation of yield after bonding, and measurement of bonding strength were performed.
[0262] <Comparative Example 3>
[0263] A film having a thickness of 12.5 μm was produced in the same manner as in Comparative Example 1. Inspection of conductive foreign matter during film production, inspection of film appearance, evaluation of yield after bonding, and measurement of bonding strength were performed.
[0264] <Comparative Example 4>
[0265] The PFA1 pellets were put into an extruder at 360°C, in which a sintered nickel filter with multiple overlapping meshes of #300 or larger was inserted between the screw and the die. The film was extruded from a 1700 mm wide T-die, pulled to a metal cooling roll, and then wound on a winding core to form a 1300 mm wide, 50 μm thick roll film.
[0266] In the same manner as in Example 1, inspection of conductive foreign matter during film formation, inspection of film appearance, evaluation of yield after bonding, and measurement of bonding strength were performed.
[0267] <Comparative Example 5>
[0268] A film having a thickness of 25 μm was produced in the same manner as in Comparative Example 4. Inspection of conductive foreign matter during film production, inspection of film appearance, evaluation of yield after bonding, and measurement of bonding strength were performed.
[0269] <Comparative Example 6>
[0270] A film having a thickness of 12.5 μm was produced in the same manner as in Comparative Example 4. Inspection of conductive foreign matter during film production, inspection of film appearance, evaluation of yield after bonding, and measurement of bonding strength were performed.
[0271] Table 2 shows the results of Examples 1 to 18.
[0272]
[0273] Table 3 shows the results of Comparative Examples 1 to 6.
[0274] [Table 3]
[0275]
[0276] From the results of Tables 2 and 3, the fluororesin film of the present disclosure can reduce the number of conductive foreign matter per square meter and can be expected to be a material for a circuit board having a good appearance and little adhesion failure with metal foil.
[0277] Industrial Applicability
[0278] The fluororesin film disclosed in the present invention can be suitably used in a metal-clad laminate for a circuit board.
Claims
1. A fluororesin film, which is a film composed of a fluororesin, wherein: The number of conductive foreign particles existing in the film and having a length of 50 μm or more in the flow direction or the width direction of the film is less than 60 pieces / m 2 .
2. The fluororesin film according to claim 1, wherein In every 1×10 6 The number of unstable functional groups of the fluororesin is less than 350 based on the number of carbon atoms in the main chain.
3. The fluororesin film according to claim 1 or 2, wherein The fluororesin is a tetrafluoroethylene / perfluoro(alkyl vinyl ether) copolymer or a tetrafluoroethylene / hexafluoropropylene copolymer.
4. The fluororesin film according to any one of claims 1 to 3, wherein The melt flow rate of the fluororesin at 372° C. and a load of 49 N is 0.1 g / 10 min to 50 g / 10 min. 5 . The fluororesin film according to claim 1 , which has an area of 1 square meter or more.
6. The fluororesin film according to any one of claims 1 to 5, wherein The conductive foreign matter includes nickel and / or carbide.
7. The fluororesin film according to any one of claims 1 to 6, wherein The bonding strength when bonding to a metal foil having a surface roughness Rz of 1.5 μm or less is 0.8 N / mm or more.
8. The fluororesin film according to any one of claims 1 to 7, which is used for a metal-clad laminate.
9. A metal-clad laminate comprising a metal foil and the fluororesin film according to any one of claims 1 to 8 as essential layers.
10. The metal-coated laminate as described in claim 9, further comprising a layer other than the metal foil and the fluororesin film, wherein the layer other than the metal foil and the fluororesin film is at least one selected from the group consisting of polyimide, liquid crystal polymer, polyphenylene sulfide, cycloolefin polymer, polystyrene, epoxy resin, bismaleimide, polyphenylene oxide, polyphenylene ether and polybutadiene.
11. The metal-clad laminate according to claim 9 or 10, wherein: The surface roughness Rz of the metal foil is 1.5 μm or less.
12. The metal-clad laminate according to any one of claims 9 to 11, wherein The bonding strength between the metal foil and the fluororesin film is 0.8 N / mm or more.
13. A circuit substrate, characterized in that: A metal-clad laminate according to any one of claims 9 to 12.
Citation Information
Patent Citations
Resin and film
JP2017119741A
Fluorine resin film and method for producing the same
JP2021160856A
Fluorinated copolymer, electric wire, and method for production of the electric wire
WO2008047906A1
Process for producing fluororesin film
WO2017022575A1